Ответ:
![\left(\dfrac{6-2\sqrt{23}}{7};\;\dfrac{6+2\sqrt{23}}{7}\right) \left(\dfrac{6-2\sqrt{23}}{7};\;\dfrac{6+2\sqrt{23}}{7}\right)](https://tex.z-dn.net/?f=%5Cleft%28%5Cdfrac%7B6-2%5Csqrt%7B23%7D%7D%7B7%7D%3B%5C%3B%5Cdfrac%7B6%2B2%5Csqrt%7B23%7D%7D%7B7%7D%5Cright%29)
Объяснение:
0\\a^2-4(a-2)(2a+1)>0\\a^2-8a^2+12a+8>0\\7a^2-12a-8\\a\in\left(\dfrac{6-2\sqrt{23}}{7};\;\dfrac{6+2\sqrt{23}}{7}\right)" alt="(2a+1)x^2-ax+a-2=0\\D=a^2-4(a-2)(2a+1)>0\\a^2-4(a-2)(2a+1)>0\\a^2-8a^2+12a+8>0\\7a^2-12a-8\\a\in\left(\dfrac{6-2\sqrt{23}}{7};\;\dfrac{6+2\sqrt{23}}{7}\right)" align="absmiddle" class="latex-formula">
Задание выполнено!